'It's just incredible the difference it has made': family carers' experiences of a specialist Lewy body dementia Admiral Nurse service. (9th October 2022) - Brown, Laura J E; Aldridge, Zena; Pepper, Amy; Leroi, Iracema; Dening, Karen Harrison
Abstract: Background: Lewy body dementia (LBD) is characterised by a complex array of symptoms. Being a family carer of someone with LBD can be challenging, and is associated with high levels of stress, depression and anxiety. Admiral Nursing services support family carers of people with dementia in the UK by providing tailored information, advice and therapeutic support. Recently, the Admiral Nurse model has been adapted to the needs of more specific populations, including the introduction of a new, specialist LBD Admiral Nurse. Objective: to explore family carers' experiences of the LBD Admiral Nurse service. Methods: fourteen family carers of people with LBD were interviewed about their experiences of the LBD Admiral Nurse service. Interview transcripts were analysed using thematic analysis. Results: four themes were identified: theme 1 described how participants valued the LBD Admiral Nurse's specialist expertise, which contrasted with the lack of knowledge they encountered in other services. In theme 2, participants described how the practical, tailored support provided by the LBD Admiral Nurse enabled them to better manage a variety of caring-related challenges. Theme 3 captured the emotional benefits that participants gained from being able to talk to someone who understood their situation. In theme 4, participants explained how the reliability of the LBD Admiral Nurse's support helped them feel supported in their role. Conclusions: the specialist knowledge and expertise of the LBD Admiral Nurse enabled family carers to better support the people they cared for, and to relieve some of the emotional stress associated with caring.